Subcloning, Expression and Characterisation of A Recombinant Antibody Fab-Fragment Specific Towards 2,4-D - Kusharyoto, Wien (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2005)
A generic strategy was established for subcloning the VH and VL gene of antibody variable domains into the plasmid pASK85 for the expression of Fab antibody fragments. pASK85 bears coding sequences for murine constant domains including a His6-tag at the carboxy-terminal end of the constant heavy-chain domain. The VH and YL gene derived from the monoclonal antibody E2/B5 specific towards 2,4-dichloropbcnoxyacetic acid (2,4- D) were used in this study. Eschericia coli was used as host cells for the biosynthesis of the Fab-fragment. The FabÂ fragment wa subsequently purified from the periplasmic extract in a single step by immobilised metal-ion affinity chromatography (IMAC). The production level obtained were 0.5-0.8 mg purified Fab-fragments per liter E. coli culture. The sensitivity and cross-reactivity of the Fab-fragment determined by direct competitive ELISA were similar to those of the parental monoclonal antibody E2/B5 . Â